Characteristics and determinants of T‐cell phenotype normalization in HIV‐1‐infected individuals receiving long‐term antiretroviral therapy. Issue 3 (31st October 2013) - Ndumbi, P; Gillis, J; Raboud, J; Cooper, C; Hogg, RS; Montaner, JSG; Burchell, AN; Loutfy, MR; Machouf, N; Klein, MB; Tsoukas, C; ,
<x xml:space="preserve">Abstract</x> Objectives Although combination antiretroviral therapy (cART) can restore CD4 T‐cell numbers in HIV infection, alterations in T‐cell regulation and homeostasis persist. We assessed the incidence and predictors of reversing these alterations with cART. Methods ART‐naïve adults (n = 4459) followed within the Canadian Observational Cohort and exhibiting an abnormal T‐cell phenotype (TCP) prior to cART initiation were studied. Abnormal TCP was defined as having (1) a low CD4 T‐cell count (< 532 cells/μL), (2) lost T‐cell homeostasis (CD3 < 65% or > 85%) or (3) CD4:CD8 ratio dysregulation (ratio < 1.2). To thoroughly evaluate the TCP, CD4 and CD8 T‐cell percentages and absolute counts were also analysed for a median duration of 3.14 years [interquartile range (IQR) 1.48–5.47 years]. Predictors of TCP normalization were assessed using adjusted Cox proportional hazards models. Results At baseline, 96% of pateints had CD4 depletion, 32% had lost homeostasis and 99% exhibited ratio dysregulation. With treatment, a third of patients had normalized CD4 T‐cell counts, but only 85 individuals (2%) had normalized their TCP. In a multivariable model adjusted for age, measurement frequency and baseline regimen, higher baseline CD4 T‐cell counts and time‐dependent viral suppression independently predicted TCP normalization [hazard ratio (HR) for baseline CD4 T‐cell count = 1.42 (1.31–1.54) per 100 cells/μL increase; P ≤ 0.0001; HR for time‐dependent suppressed viral load = 3.69 (1.58–8.61); P‐value ≤ 0.01]. Conclusions Despite effective cART, complete TCP recovery occurred in very few individuals and was associated with baseline CD4 T‐cell count and viral load suppression. HIV‐induced alterations of the TCP are incompletely reversed by long‐term ART.